Organizational Identification: A Bibliometric Analysis and Mapping the Field - Darko Tipurić; Mislav Radić; Lana Cindrić (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This paper reviews the literature on organizational identification. In order to organize the vast theoretical and empirical findings of the topic, we have conducted a cross-disciplinary bibliometric analysis and systematic literature review based on 470 journal articles from the Web of Science Core Collection. The primary aim of the study was to provide structure and clarity to a scattered and extensive body of literature on organizational identification. Also, it was to map the intellectual terrain and find common threads and intellectual twists within the selected sample of articles. Based on a large set of keywords, we carried out a multiple correspondence analysis which provided us with a two-dimensional model illustrating the keywords based on their importance and proximity. The resulting four quadrants were analyzed in terms of their overlaps and distinctions.
Keywords: 650; Organisational identification; Identity; Bibliometrics; Multiple Correspondence Analysis; Systematic Literature Review